Preparation and electrical properties of polypyrrole containing photocured thiol-ene based composites - DUMLUDAĞ, FATİH; KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (ELSEVIER SCIENCE SA, 2015)
In this study, UV curable polypyrrole containing thiol ene based composite films were prepared by the reaction between Propoxylated (2) neopentyl glycol diacrylate (SR 9003), Trimethylolpropane tris(3-mercaptopropionate), (3-mercaptopropyl)trimethoxysilane, 1-vinyl-2-pyrrolidinone and polypyrrole. FT-IR was used to confirm the formation of the composites. Thermal stability of the samples was evaluated by thermogravimetric analysis (TGA). The samples were characterized with the following analysis; gel content, water absorption capacity. Hydrophobicity of the samples was determined by the contact angle measurements. Direct current (dc) conductivity measurements of samples were performed depending on polypyrrole content in the composites at room temperature. Capacitance measurements (40 Hz-100 kHz) of the samples were performed in the temperature range of 295-378 K. Dc conductivity and capacitance values of the samples were measured in vacuum in dark. Dc conductivity measurements revealed that dc conductivity values increased with increasing polypyrrole content. Dielectric measurements revealed that dielectric constant of the samples increased with increasing temperature and decreased with increasing frequency. It is also observed that dielectric constant of the samples decreased with increasing polypyrrole content. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: UV curing; Thiol-ene; Polypyrrole; Thermal properties; Dielectric properties; POLYMERIZATION; PHOTOPOLYMERIZATION; CHEMISTRY; FILMS